Linear cavity Brillouin fiber laser using a fiber Bragg grating - Ahmad, Harith; Shirazi, Mohammadreza Rezazadeh; Biglary, Mozhgun; Harun, Sulaiman Wadi (John Wiley & Sons, 2008)
An efficient linear cavity Brillouin fiber laser (BFL) is demonstrated using a standard single mode fibre (SMF), an optical coupler and a fiber Bragg grating (FBG). The laser peak is obtained at -4.5 dBm with a Brillouin pump of 14 dBm. The use of a 99/1 optical coupler shows the highest output because of the low loss in the cavity. The BFLs can be used to reduce the laser linewidth and technical noise. PACS: 42.60.Da; 42.81.-i; 42.81.Wg; 42.81.Uv